Reduction of post-harvest losses through estimation of open air-drying period of agricultural products of mass consumption: case of Benin - ADOUNKPE, GNONLONFOUN JULIEN; HOUNGUE, Guy Hervé; Vitouley, Armel; AMOUSSA HOUNKPATIN, WALIOU BODOURIN AYANDA; Vitouley, Armel; AHOUANNOU, CLÉMENT; KOUNOUHEWA, Basile (My University, 2021)
problem which deserves special attention, worldwide. In this work, agro-meteorological parameters collected at different weather sta tions of Benin Republic were analysed in order to highlight their seasonality, and to identify favourable air-drying periods for agricul tural products. Periods from March to May and October to December have the peaks of global radiation and insolation; high temperatures values are concentrated between February and May, and rains sequences are observed from March to November. Cross-analysis of different parameters led to statistically identifying favourable drying periods for agricultural products in each region of the country. The period from November to February was shown to be favourable. It includes most post-harvest periods for most of the cultivated agri cultural products and also has the best environmental and practical conditions for natural air-drying.
Keywords: Agricultural products; post-; harvest losses; Benin